Risk-Generating aspect of public history in digital environment (on the example of Russian video blogging in the 2020s) - Yu. V. Nikulich (Цифровая социология)
The article contains materials of a sociological study of public history sociocultural practices in social media. Based on the analysis of data from in-depth interviews with experts in the field of media history (N = 60) conducted in 2022-2023, a classification of the main risks that a historian faces on the Web has been compiled. The concept of digital capital was used as a theoretical framework, considering it as a relevant component of cultural, symbolic, and social types of capital. Digital transformation of society, including education system, is a factor in digitalization and democratization of knowledge. In this process, academic communities, commercial projects, initiative groups, and individual citizens face a number of risks associated with acquisition and realization of their capitals. The analysis of the research results allowed us to conclude that the relevant sources of risks are the communicative and financial side of activity. The issue of confrontation between academic community and digital popularizers of history remains debatable, as experts point out the danger of deprofessionalization in case of excessive audience orientation. Since riskiness goes hand in hand with societal instability, uncertainty, and hypervariability, political and corporate suppression of certain discourses and dynamic development of information and communication technologies have been highlighted as risks. The latter creates both risks and potential for public history development, historians mastering a new set of competences and obtaining differentiated sources of income. In this process, intangible capital is converted into material capital, actualizing the financial side of practices.